Model Organisasi Kurikulum Berbasis Pesantren Pada Mata Pelajaran PAI di Pondok Pesantren Raudhatus Salaam Yogyakarta: The Organizational Model of Pesantren-Based Curriculum in Islamic Education (PAI) Subjects at Raudhatus Salaam Islamic Boarding School, Yogyakarta - Iis Siti Khoiriyyah; Mela Mariana; Afrihadi; Muhammad Akbar (Educan, 2025)
This study aims to examine the curriculum organization model based on pesantren in Islamic Education (PAI) subjects at Raudhatus Salaam Islamic Boarding School, Yogyakarta. The curriculum, as a systematic educational program, plays a significant role in shaping students' character and competencies, particularly in the modern era, which demands a balance between religious and academic education. This research employs a qualitative approach with a descriptive analysis method. Data were collected through observations, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal that the PAI curriculum in this boarding school adopts an integrated curriculum model, combining the Ministry of National Education curriculum and the Kulliyatu-l-Mu’allimin Al-Islamiyah curriculum from the Modern Islamic Boarding School Darussalam Gontor. This approach fosters synergy between national academic education and the unique Islamic education of pesantren. The model is relevant for further development in the context of Islamic education in Indonesia, especially in addressing the challenge of integrating religious values with formal education requirements. This study contributes to the development of a more adaptive pesantren curriculum design, offering practical solutions for Islamic educational institutions to address contemporary challenges.